THE EFFECT OF LEARNING VIDEO MEDIA ON THE STUDENTS' III GRADE SCIENCE LEARNING OUTCOMES AT SDN 6 MALAKA - Mujtahid Mujtahid (PROGRES PENDIDIKAN, 2022)
This study aims to conduct research on the Effect of Learning Video Media on Science Learning Outcomes of Third Grade Students of State Elementary School 6 Malacca. Learning video media will be useful to make it easier for students to understand the subject matter and determine the success of a learning process. The research method used is a quantitative method. The form of research used is experimental research. This research was carried out at SDN 6 Malaka. The variables used in this study were independent variables and research variables. The independent variable in this case is learning video media, while the other variables are learning outcomes. The population in this study were students of class III A and B, totaling 44 students. Based on the data from the t test, the data obtained are sig > 0.05, and sig = 0.00. So it can be said that there is a very important difference in the results of learning science class III SDN 6 Malaka, between students who learn to use learning video media and those who do not use learning video media.